Tailoring social safeguards in conservation to reflect the local context and level of risk. Issue 8 (17th June 2022) - Wilkie, David; Kretser, Heidi E.; Painter, Michael; O'Brien, Faye; Holmes, Alexa; Mastro, Kathryn; Wieland, Michelle; Sriskanthan, Gayathri; Mangubhai, Sangeeta; Jupiter, Stacy; Painter, Lilian; Chetkiewicz, Cheryl
Abstract : This evidence piece argues that social safeguards in the context of conservation should not be put in place using a formulaic, one size fits all approach Rather safeguards should be tailored to the conservation approaches and actions being implement and the social risks. The piece uses the Wildlife Conservation Society as an example of how a tailored approach is being implemented in the field.